Titanium superoxide catalyzed selective oxidation of phenols to p-quinones with aq. H2O2 - Dewkar, Gajanan; Shaikh, T. M.; Pardhy, S.; Kulkarni, S. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
Titanium superoxide, a novel heterogeneous and readily accessible catalyst, is found to catalyze the selective oxidation of phenols to the corresponding 1,4-benzoquinones in preparative yields with aq. 30% H2O2 as oxidant under mild reaction conditions.